Scheduling Part-Families Under FMS: To Mix or Not to Mix? - CO, Henry C. (Institutional Knowledge at Singapore Management University, 2001)
This paper considers the issue of whether to mix part-types in one or several of the families to be produced in a flexible manufacturing system (FMS). For this input control problem in an FMS, we have derived conditions that support the mixing of a part-type, which can share the setup of other part-types, in deterministic environment. The problem is identified as a special economic lot scheduling problem (ELSP), and is formulated as a linear programming problem. Analytical insights are derived by considering the special case with three part-families. The results are illustrated with a numerical example.